Application Of Tig-Mig Hybrid For Wire Arc Additive Manufacturing (Waam) - Seah Rey Kar (2022)
Wire arc additive manufacturing (WAAM) is an advanced fabrication technology in three-dimensional (3D) printing that deposited metal material layer-by-layer using electric arc as a heat source to form the final part. However, the excessive heat input was the major challenge of manufacturing WAAM will cause coarsening in microstructure that affects the mechanical properties. The aim of this study for TIG-MIG hybrid welding was applied in wire arc additive manufacturing (WAAM) to investigate the microstructure formation in each welding layer as an effect of multilayer welding. The main parameter of TIG-MIG hybrid welding included current (A), voltage (V), torch configuration of TIG-MIG hybrid, welding speed and wire feeding rate were investigated in this research project. The TIG-MIG hybrid was reduced the heat input and surface temperature gradient compared to conventional MIG. The Infrared Thermometer analysed the heat accumulation for the T1G-MIG hybrid was lower than that of the conventional MIG. The weld bead geometry of the T1G-MIG hybrid had higher reinforcement but lower penetration and smaller weld bead width compared to conventional MIG. The microstructure observation of TIG-MIG hybrid has a finer microstructure whereas conventional MIG has a coarser microstructure. These microstructures were analysed by microhardness test resulting in TIG-MIG hybrid had lower hardness than conventional MIG welding techniques. Consequently, it can be proved that the microstnicture formation of the TIG-MIG hybrid can be a refinement to enhance mechanical properties. Keywords: Wire Are Additive Manufacturing (WAAM), TIG-MIG hybrid, Conventional MIG, Microhardness, Heat input, Heat accumulation